A comparative study of the oral condition between the institutionalized mentally handicapped and normal schoolchildren in Metro Manila, 1983 - Pangan, Elfleda Lilia J.
A comparative study of the DMFT, Gingival and Debris indices was made between mentally handicapped and normal children in Metro Manila. Thirty-nine subjects from four training institutions were matched with thirty-nine normal school children in terms of age, sex and economic status. The results show that there is a significant difference between the oral condition of mentally handicapped and normal children. With the exception of the Debris Index, it appears that the DMFT and Gingival Index scores are higher in the former than the latter.